KONSTRUKSI NASIONALISME DALAM NOVEL-NOVEL INDONESIA PRAKEMERDEKAAN (STUDENT HIJO DAN SALAH ASUHAN ) - Wiyatmi, Wiyatmi (Sekolah Pascasarjana UGM, 2013)
This paper aims to discuss construction of nationalism contained in Indonesian novels preindependence,Â especially Student Hijo and Salah Asuhan using perspective hegemony Gramsciâs theory. The analysisÂ showed that both the novel construct of ideology of nationalism against colonialism in the Dutch colonialÂ era. Both novels also showed his duties as a battle field of ideology of nationalism against colonialism.